PENGARUH TOXIC LEADERSHIP, JOB STRESSDAN PERCEIVED ORGANIZATIONALSUPPORT TERHADAP TURNOVER INTENTION PADA KARYAWAN DI PT. KELAPA SAWIT GSB EMPAT LAWANG - Eti Arini; Kurniawan Agusman (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2026)
This study aims to analyze the influence of toxic leadership, job stress, and perceived organizational support on turnover intention in case study employees at PT galempa Sejahtera Bersama Simpang Perigi Empat Lawang Branch. This research uses quantitative methods with a survey approach, where data is obtained through questionnaires distributed to 60 respondents. The results of this study confirm that psychological, social and support factors have a significant influence on individual exit intentions. This underscores the importance of positive leaders and a healthy work environment as well as support from the company in maintaining employee engagement. Therefore, organizations need to implement policies to improve leadership quality, effectively manage work stress, and increase the level of support perceived by employees to lower high exit intentions. A decrease in exit intention can be achieved through improving a healthy and supportive work environment. Keywords: Toxic Leadership, Job Stress, Perceived Organizational Support, Turnover Intention